Visible-Light Photocatalytic Barbier-Type Reaction of Aziridines and Azetidines with Nonactivated Aldehydes - Qu, Quan; Chen, Lin; Deng, Yu; Gui, Yong-Yuan; Yu, Da-Gang (Synlett, 2023)
Barbier-type reactions are a classic group of reactions for carbon–carbon bond formation; however, their common use of stoichiometric metals restricts their widespread application. Considering the ready availability and diversity of cyclic amines, we report a visible-light photocatalytic Barbier-type reaction of aziridines and azetidines with nonactivated aldehydes. A series of important γ- and δ-amino alcohols were synthesized in the presence of amines as electron donors. Moreover, this transition-metal-free protocol displays mild reaction conditions, broad functional-group tolerance, and a wide substrate scope. Mechanistic investigations indicated that carbon radicals and carbanions might be generated as key intermediates.
Keywords: photocatalysis; Barbier reaction; aziridines; azetidines; C–N bond cleavage